J. H. Prynne's moral cosmology. Issue 7 (9th August 2019) - Luker, Ed
ABSTRACT: This article approaches the poetic development between J. H. Prynne's The White Stones and Brass . It explores this development through the use of cosmology in both books. It traces the figure of the stars across The White Stones and into their appearance in 'The Ideal Star-Fighter' in Brass . It examines how the stars start as figures of patience and become the instantiation of an urgent moral imperative. This image of the stars as a figure of eschaton is contrasted to Prynne's comments on Charles Olson's Maximus IV, V, VI, to highlight their distinctions. It then articulates how with 'The Ideal Star-Fighter' this former cosmological imperative twists into a lament. The poem is examined as a work that exhibits sharp contrasts between two modes of poetic thought, as being trapped between two tendencies within Prynne's writing. The impossibility of the moral imperative is explored through the context of technological advancements that were made possible by the experiments of scientific cosmology, especially in relation to the Cold War and the Vietnam War. Through close reading of particular poems in combination with archival materials, it aims to contextualise the shift within Prynne's poetic thought by ventilating the work through its historical context.